π‐Bridged Dimer Strategy of Aggregation‐Induced Emission Molecules to Achieve Very Strong Absorption Ability - Liwei Dou; Huanlong Zheng; Haonan Xiong; Shengjie Fu; Chenguang Wang; Di Li (Aggregate)
ABSTRACT Aggregation‐induced emission (AIE) molecules have attracted widespread attention due to their remarkable fluorescence properties in the aggregated state. However, the highly twisted structures of AIE molecules significantly disrupt the π‐conjugations, thus resulting in weak absorption abilities (i.e., small molar absorption coefficients ε). To overcome this problem, herein we have proposed an efficient molecular design strategy: π‐bridged dimer of AIE molecules. Accordingly, two series of AIE dimer molecules, TPE‐BTO‐Dimer 1‒6 and DTPE‐BTO‐Dimer 1‒6 with various π‐bridged moieties, have been newly synthesized. In comparison to the corresponding AIE monomer molecules TPE‐BTO and DTPE‐BTO, the dimer molecules retain the AIE character while exhibit largely improved absorption abilities (the ε values are increased by 2.3‒3.7 times to 6.01‒9.54 × 104 M−1 cm−1) as well as significantly redshifted absorption maxima. The theoretical calculations have revealed that the π‐bridged dimer strategy dramatically increases the oscillator strength of electron transition from the ground state to an excited state and thus results in a large ε. In the transient absorption studies, the local excited state components of dimer molecules are obviously higher than those of monomer molecules, which further confirms the effectiveness of π‐bridged dimer strategy. Moreover, one of the AIE dimer molecules DTPE‐BTO‐Dimer 6 with near‐infrared (NIR) emission has been applied in NIR fluorescence imaging‐guided photothermal therapy. The very strong absorption ability has enabled its nanoparticles to exhibit a high photothermal conversion efficiency of 73% under the 655 nm laser irradiation and thus display a desired photothermal therapy performance.